SISTEM INFORMASI PENILAIAN KARYAWAN PADA PT. HIBA UTAMA MENGGUNAKAN METODE SAW - Malfiany, Rini; Sobirin, Sobirin (Jurnal Komputer dan Teknologi, 2025)
Employees are one of the supporting factors for the success of an agency or company. With employees who meet the company's qualification standards, company productivity will certainly be maintained and increased. The process of selecting high-performing employees is a process that requires various kinds of careful and complex considerations because of the many criteria being assessed. In order to obtain information on employee performance quickly, precisely and accurately, technology is needed for the automation process. Therefore, to meet these information needs, a web-based system is needed. In addition, employee assessments at PT. Hiba Utama still use the Ms Excel format, so this is the basis of the research. The research conducted is to create a web-based information system as a consideration for conducting employee assessments at PT Hiba Utama. The method used to facilitate employee assessment, researchers use the Simple Additive Weighting method, where the system will provide a sequential value or ranking according to the quality of the employee assessment. The results of this research are an assessment system that will become a decision support system for producing high-performing employee selection.